PENGARUH ISAP LENDIR (SUCTION) SISTEM TERBUKA TERHADAP SATURASI OKSIGEN PADA PASIEN TERPASANG VENTILATOR - Saifudin Zukhri; Fitri Suciana; Agus Herianto (MOTORIK Jurnal Ilmu Kesehatan, 2018)
Patients who are attached to endotracheal tube and ventilator will requiring endotracheal tube suctioning that can causes hypoxemia. In ICU RSUP dr. Soeradji Tirtonegoro, the open endotracheal tube suctioning was performed using a general suctioning SOP. Credland has developed an open endotracheal tube suctioning procedure based on recent literature and research. The aim of this research is to know the difference of the effect of open endotracheal tube suctioning that done in ICU with open endotracheal suctioning by Credland on the peripheral oxygen saturation of the patient who installed ventilator.This research uses “quasi experiment” design with “pre test and post test nonequivalent control group” and uses “consecutive sampling”. Ten respondents became the control group when an open endotracheal tube suctioning was applied using generalized SOP in ICU and became the treatment group when was applied with the Credland method. Statistical analysis to determine the peripheral oxygen saturation difference in each group using “wilcoxon”. To compare the oxygen peripheral saturation difference in the control group and the treatment group using “mann whitney”. In the control group the mean of oxygen peripheral saturation before suctioning was 97.8 ± 2.4 and after suction was 94.2 ± 3.0 with the mean difference before and after the suctioning was 3.6 ± 1 , 5. In the treatment group the mean of oxygen peripheral saturation before suctioning was 97.4 ± 3.2 and after suctioning was 95.7 ± 4.9 with average saturation difference before and after suctioning was 1.7 ± 2, 2.There was a difference in the effect of an open endotracheal tube suctioning that done in ICU with open endotracheal tube suctioning by Credland’s methode on the peripheral oxygen saturation of the ventilator-installed patient with p value = 0.014 (p <0.05)